Annexin in plants - Phang, Ing Chia (2006)
Annexins are a diverse, multigene family of Ca2+-regulated phospholipids and membrane-binding protein. An annexin-like protein in higher plants was first discovered in 1989. Up to 0.1% of the total extractable protein in plant cells could be annexins. Annexins possess the characteristic four repeats of 70 to 75 amino acids and possess the sequence GXGTD motif within the endonexin in the C-terminal domain fold for calcium binding. This conserved C-terminal domain, the “annexin core”, is α-helical and forms a compact disk with a slight curvature. The variation of the N-termini of the different annexins in sequence and length is an important basis of functional differences. Immunolocalization studies reveal